Pemberian Reward terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening - Liana, Yuyuk; Putra, Julio C; Djafri, Taufik; Lating, Ali (Al-Amien Prenduan for Islamic Institute, 2024)
The purpose of this study was to analyze the reward (X) indirect effect on employee performance through work motivation (Z). The population in this study were all employees of PT Indolakto Pandaan, totaling 300 people. The sampling technique was carried out by random sampling method, namely 172 respondents. Data analysis techniques using descriptive statistics and path analysis with Partial Least Square (PLS). The results showed that the results showed that Reward had a direct effect on employee performance. Reward has a direct effect on employee performance mediated by employee work motivation, and reward has an indirect effect on employee performance through work motivation at PT Indolakto Pandaan. The contribution of reward, work motivation to explain employee performance is 59.6%. So there are still 40.4% other factors that affect employee performance.